Trafficking in illicit firearms: a global and European overview : in the framework of the project ‘The development of the observatory function of the European Centre of Expertise on Crime Prevention within the EUCPN’ -EUCPN Secretariat, February 2015, Brussels - Meijers, Loy (Theoretical paper, 2015)
This theoretical paper is published by the EUCPN Secretariat in connection with the theme of the Dutch Presidency, which is trafficking in illicit firearms. With the terrorist attacks that shook Europe the past months in hindsight, the subject is more relevant than ever. Trafficking in illicit firearms is a dangerous and deadly business, which should not be taken lightly. Because of the cross-border aspect of trafficking in illicit firearms, it is important to have a global overview. Where do the weapons come from, how do they enter the illicit market and what are the modus operandi of the traffickers? This paper should function as a base for a more prevention-orientated manual in which we will look at the difficulties and attempts to prevent trafficking in illicit firearms. Furthermore we will focus at the main international weapons and what the international agencies already do against the phenomenon. Through these actions, we hope to raise awareness concerning trafficking in illicit firearms, to exchange good practices and hopefully to propose general guidelines for a trafficking in illicit firearms policy.